Affective and Enjoyment Responses to Sprint Interval Training in Healthy Individuals: A Systematic Review and Meta-Analysis - Hu, Mingzhu; Jung, Mary E.; Nie, Jinlei; Kong, Zhaowei (Frontiers in Psychology, 2022)
Sprint interval training (SIT) is characterized by intensity of “all-out” effort and superior time-efficiency compared to traditional moderate-intensity continuous training (MICT) and has been proposed as one viable solution to address the commonly reported barrier of lack of time for physical activity. While substantial physiological benefits of participation in SIT have been well-documented, the psychological responses to SIT are less clear. No systematic review has been conducted thus far to respond to the assumption that its supramaximal intensity will induce adverse feelings. Therefore, the aim of the present study was to synthesize studies analyzing affective and enjoyment responses to SIT and to compare the responses to SIT with MICT and other high intensity interval training (HIIT) protocols with lower intensities. After searching relevant databases up until 22nd March 2021, twenty-eight studies meeting the inclusion criteria were included in the present review. Random effect meta-analysis using the pooled data demonstrated that SIT induced similar post-exercise affective valences during the training compared to MICT and HIIT, but lower affective valences immediately post-exercise compared to MICT. Moreover, affective responses during SIT decreased to negative valences according to the results from most included studies, while low-volume SIT protocols with shorter sprint duration and repetitions induced more positive affective responses. Level of enjoyment after SIT were positive and were comparable to MICT or HIIT. Overall, the results from the existing literature indicate that SIT could be a more time-efficient and enjoyable and pleasurable training modality for healthy individuals in relation to MICT or HIIT, despite its supramaximal intensity. Low-volume SIT may be a realistic option for individuals seeking a time-efficient workout with comparable affective responses to MICT or HIIT.